From Northern Ireland to Afghanistan: half a century of blast injuries. Issue 1 (23rd February 2019) - McGuire, Ruth; Hepper, A; Harrison, K
Abstract : Introduction: Throughout the last half century, blast injuries have been a common occurrence to UK military personnel during combat operations. This study investigates casualty data from three different military operations to determine whether survivability from blast injuries has improved over time and whether the tactics used could have influenced the injuries sustained. Methods: Casualty data from operations in Northern Ireland, Iraq and Afghanistan were reviewed and found to contain a total of 2629 casualties injured by improvised explosive devices. The injury severities were examined and the suitability of comparison between conflicts was considered. Results: The case fatality rate and mean severity score sustained remained consistent among the operations included in this study. Using the New Injury Severity Score, the probabilities of survival were calculated for each separate operation. The body regions injured were identified for both fatalities and survivors. Using this information, comparisons of injury severities sustained at an Abbreviated Injury Scale of 3 and above (identified as a threshold for fatal injury) were conducted between the different operations. Conclusions: The data showed that as operations changed over time, survivability improved and the proportions of body regions injured also changed; however, this study also highlights how studying casualty data from different conflicts without taking account for the contextual differences may lead to misleading conclusions.